Audit Challenges dalam Industri Fintech dan Cryptocurrency: Perspektif Regulatory Compliance dan Technology Risks - Bulan Karima Nurani (Universitas Ngudi Waluyo, 2022)
The rapid development of financial technology (fintech) and cryptocurrency creates new complexities in audit practices. This research analyzes audit problems in fintech companies focusing on regulatory compliance and technology risks, audit procedures for crypto assets and blockchain-based transactions, and audit methodology for peer-to-peer lending platforms. The study uses a qualitative approach with literature analysis and case studies of 15 fintech companies in Indonesia for the period 2020-2024. Results show that auditors face difficulties in understanding blockchain technology (78% of respondents), crypto asset validation (65%), and cyber risk assessment (82%). Peer-to-peer lending platforms require specific procedures in assessing credit quality and loss reserves. The research recommends developing specific audit standards for the fintech industry and improving auditor competence in digital technology. Abstrak Perkembangan pesat teknologi finansial dan mata uang kripto menciptakan kompleksitas baru dalam praktik audit. Penelitian ini menganalisis problematika audit pada perusahaan teknologi finansial dengan fokus pada kepatuhan regulasi dan risiko teknologi, prosedur audit untuk aset kripto dan transaksi berbasis rantai blok, serta metodologi audit platform pinjam meminjam berbasis teknologi. Studi menggunakan pendekatan kualitatif dengan analisis literatur dan studi kasus pada 15 perusahaan teknologi finansial di Indonesia periode 2020-2024. Hasil menunjukkan bahwa auditor menghadapi kesulitan dalam memahami teknologi rantai blok (78% responden), validasi aset kripto (65%), dan penilaian risiko siber (82%). Platform pinjam meminjam berbasis teknologi memerlukan prosedur khusus dalam menilai kualitas kredit dan cadangan kerugian. Penelitian merekomendasikan pengembangan standar audit spesifik untuk industri teknologi finansial dan peningkatan kompetensi auditor dalam teknologi digital.